Developing Student Morals at the Integrated Islamic High School (SMA IT) Al-Madaniyah Samuda - As Ari, Miftahul; Muslimah, Muslimah; Hidayati, Noorazmah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
Moral development at SMA IT Al-Madaniyah Samuda has a very crucial role in the process of character formation of students. This school is committed to not only producing individuals who excel in academics, but also forming individuals with noble morals and are able to apply Islamic values in everyday life. Therefore, moral development is an integral part of the educational process given to students. The purpose of this study is to describe and analyze the moral development applied to students at SMA IT Al-Madaniyah Samuda and to identify the challenges faced in the process of moral development. This study uses a qualitative approach with a descriptive design, the data sources in this study are students, parents of students, and the principal. Data collection techniques used in this study are observation, interviews, and documentation. The data validation technique used in this study is source triangulation. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusions. The results of the study indicate that moral development is carried out using various methods, such as lectures, questions and answers, discussions, and role models. In addition, there are several obstacles in the implementation of moral development, including differences in family background, time constraints, and variations in the role of teachers in implementing moral development.